2014
DOI: 10.1002/dta.1737
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and selected pharmacodynamics of cobalt following a single intravenous administration to horses

Abstract: Cobalt has been used by human athletes due to its purported performance-enhancing effects. It has been suggested that cobalt administration results in enhanced erythropoiesis, secondary to increased circulating erythropoietin (EPO) concentrations leading to improvements in athletic performance. Anecdotal reports of illicit administration of cobalt to horses for its suspected performance enhancing effects have led us to investigate the pharmacokinetics and pharmacodynamic effects of this compound when administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 17 publications
2
66
2
1
Order By: Relevance
“…Prior to the study, horses were exercised five days a week as described previously. [9] The general exercise protocol was meant to simulate the strenuous exercise of race training. All horses were subject to regular fitness testing, including weekly heart rate measurements and calculation of V 200 (running velocity that elicited a heart rate 200 bpm) and monthly measurements of end-run plasma lactate concentrations, as a means of ensuring that the fitness level of the horses used in this study were as comparable as possible to the average Thoroughbred racehorse.…”
Section: Experimental Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the study, horses were exercised five days a week as described previously. [9] The general exercise protocol was meant to simulate the strenuous exercise of race training. All horses were subject to regular fitness testing, including weekly heart rate measurements and calculation of V 200 (running velocity that elicited a heart rate 200 bpm) and monthly measurements of end-run plasma lactate concentrations, as a means of ensuring that the fitness level of the horses used in this study were as comparable as possible to the average Thoroughbred racehorse.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Samples were collected as described previously. [9] Catheters were removed following collection of the 18-h sample and the remaining samples collected by direct venipuncture. Blood samples were collected into ethylenediaminetetraacetic acid (EDTA) blood tubes (Kendall/Tyco Healthcare, Mansfield, MA, USA) and stored on ice until centrifugation at 3000 x g for 10 min at À4 C. Plasma was then immediately transferred into storage cryovials (Phenix Research Products, Chandler, NC, USA) and stored at À20 C until analysis (approximately 2 weeks following collection of the final sample).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Knych et al [41] , Ho et al [42] Ho et al [42] Nickel Schaumloffel et al [44] --Xenon, krypton -Thevis et al [48] -…”
Section: Gnrhunclassified
“…The results showed that a single administration of cobalt had no effects on EPO concentrations, red blood cells parameters, or heart rate in any of the horses studied and no adverse effects were reported. [41] The study suggested that regulators should be able to detect administration of a single dose of cobalt to horses. Ho et al [42] conducted an extended study in which the proposed threshold concentrations of 2 ug/L in plasma and 75 ug/L in urine could be used as control limits for the detection of cobalt in horses on race-days.…”
Section: Cobaltmentioning
confidence: 99%
“…A recent study examined the pharmacokinetics and pharmacodynamics of cobalt following intravenous (IV) administration to 18 horses (Knych et al, 2014). The authors showed that a single IV dose of cobalt chloride or cobalt gluconate had no effect on EPO concentrations, red blood cell parameters or heart rate in any of the horses studied.…”
Section: Introductionmentioning
confidence: 99%